Covalently Interlocked Cyclohexa-m-phenylenes and Their Assembly: En Route to Supramolecular 3D Carbon Nanostructures - Dumslaff, Bastian; Reuss, Anna N.; Wagner, Manfred; Feng, Xinliang; Narita, Akimitsu; Fytas, George; Mueller, Klaus (Angewandte Chemie International Edition, 2017)
In our search to cluster as many phenylene units as possible in a given space, we have proceeded to the three-dimensional world of benzene-based molecules by employing covalently interlocked cyclohexa-m-phenylenes, as present in the unique paddlewheel-shaped polyphenylene 10. A precursor was conceived, in which freely rotating m-chlorophenylene units provide sufficient solubility along with the necessary proximity for the final ring closure to give 10. Monitoring the assembly of solubilized tert-butyl derivatives of 10 into supramolecular carbon nanostructures by dynamic light scattering (DLS) and Brillouin light scattering (BLS) revealed the dimensions of the initially formed aggregates as well as the amorphous character of the solid state.
CRIS-Team Scopus Importer:2023-03-20
Keywords: macrocycles; nanostructures; polyphenylenes; supramolecular chemistry; synthesis design